2014
DOI: 10.1152/ajpgi.00116.2013
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor plays a role in the regulation of liver and plasma lipid levels in adult male mice

Abstract: Dsk5 mice have a gain of function in the epidermal growth factor receptor (EGFR), caused by a point mutation in the kinase domain. We analyzed the effect of this mutation on liver size, histology, and composition. We found that the livers of 12-wk-old male Dsk5 heterozygotes (+/Dsk5) were 62% heavier compared with those of wild-type controls (+/+). The livers of the +/Dsk5 mice compared with +/+ mice had larger hepatocytes with prominent, polyploid nuclei and showed modestly increased cell proliferation indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
(64 reference statements)
1
36
0
Order By: Relevance
“…2. EGFR has been verified to play a regulatory role in hepatocyte proliferation and plasma lipid metabolism in adult male mice25. The livers of Dsk5 mice, an animal model with gain of function in EGFR, exhibited decreased hepatic LDL receptor (LDLR) expression as well as fatty acid synthase (FAS) expression, providing metabolic mechanism for the elevated plasma LDL.…”
Section: Resultsmentioning
confidence: 99%
“…2. EGFR has been verified to play a regulatory role in hepatocyte proliferation and plasma lipid metabolism in adult male mice25. The livers of Dsk5 mice, an animal model with gain of function in EGFR, exhibited decreased hepatic LDL receptor (LDLR) expression as well as fatty acid synthase (FAS) expression, providing metabolic mechanism for the elevated plasma LDL.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 39.6% of chemotherapy patients on gefitinib, a small molecule EGFR inhibitor, developed abnormal liver function (Wang and others 2016). Further, loss of EGFR function in humans and mice is implicated in the development of steatosis (Collin de l’Hortet and others 2014; Scheving and others 2014). EGFR activation was shown to be hepatoprotective against chemical-induced liver injury and EGF supplementation attenuated alcohol-induced liver disease (Deaciuc and others 2002; Scheving and others 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Akt and mTOR are effector kinases downstream of EGFR that regulate lipid metabolism, and glycogen synthesis (Caron and others 2015; Taniguchi and others 2006). Decreased EGFR signaling has been implicated in metabolic diseases such as type II diabetes (Bernal-Mizrachi and others 2014; Miettinen and others 2008) and NASH (Collin de l’Hortet and others 2014; Deaciuc and others 2002; Komposch and Sibilia 2016; Scheving and others 2014; Scheving and others 2015), both of which have been associated with PCB exposures (Cave and others 2010; Li and others 2013; Taylor and others 2013; Wahlang and others 2016; Wahlang and others 2014b; Yu and others 1997). Thus, we hypothesised that if PCBs antagonised EGFR like phenobarbital, this mechanism could account for both indirect CAR activation and the associated ‘off target’ effects contributing to PCB-related NASH.…”
Section: Introductionmentioning
confidence: 99%
“…ERBBs were linked to metabolic regulation as early as 1965, when Stanley Cohen found that injection of EGF into newborn rodents induces fatty liver (including some elevation in cholesteryl esters) ( 44 ), and now reinforced with the finding that the Dsk5 gain-of-function mutation in the EGFR induces fatty liver with elevated HMGCR and FAS in mice ( 45 ).…”
Section: Discussionmentioning
confidence: 99%